Empowerment of the Indonesian Red Cross Organization (IRCO) as a Convenience of Knowledge Healthy and Clean-Living Behavior (HCLB) during the Covid-19 Pandemic in the School through Graphic Design Media - Yusma Indah Jayadi; A. Syamsiah Adha; Nurul Inayah Tompo; Nur Intan Utami; Anita Yudianti (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2022)
he impact of the lack of Clean and Healthy Living Behavior (HCLB) is a learning atmosphere that is less comfortable due to a dirty environment, lowers enthusiasm for learning, and reduces the good image of the school in the general public. Diseases that occur in school-age children such as diarrhea, intestinal worms, anemia, dengue fever are related to Clean and Healthy Living Behavior. This community empowerment program aims to provide information with the aim of increasing knowledge about clean and healthy living behavior (HCLB) through graphic design media during the COVID 19 pandemic. Theain material for this training was an overview of HCLB in general and HCLB that is more specific in school settings during the COVID 19 pandemic, as well as showing examples of graphic design to practice skills as an educational medium. The program targets were members of IRCO MAN 2 Makassar City. The first activity, namely the empowerment team from UIN Alauddin Makassar, first conducted a problem analysis by making IRCO members as partners. The second activity was advocacy by conducting program presentations, getting support from the school, their willingness to work together, and sharing team work with partners. The third activity, namely building an atmosphere, which was carried out by training and mentoring partners to become cadres, will be held on March 8-9, 2022. Assistance in making graphic designs on March 10, 2022. The number of students who were trained were 12 students who were members of IRCO as prospective peer counselors with the paired sample t-test, a 2-tailed significance value of 0.013 < 0.05, indicating a significant difference in pre- and post-test knowledge. The last activity is a community movement which is carried out in the form of implementing the previous peer educator training. The results obtained from 36 peer participants using the Wilcoxon test, known as Asymp.Sig. (2-tailed) is worth 0.000< 0.05. The results show that there is an effect of implementing empowerment on cadres and peers regarding HCLB in the school setting.